Peran Sekolah Seni Tubaba Dalam Membentuk Identitas Budaya Lokal di Kabupaten Tulang Bawang Barat - ahmadi, habib; Hidayati, Dewi Ayu; Rochana, Erna (Journal Social Politica, 2025)
This study aims to examine the role of Sekolah Seni Tubaba in shaping the local cultural identity of Tulang Bawang Barat Regency. Using a qualitative approach, data were obtained through observation, interviews, and documentation, with informants directly involved in learning and artistic activities. The findings show that Sekolah Seni Tubaba plays an important role in preserving and developing local culture through cross-disciplinary and adaptive art education. The school grants students the freedom to explore their artistic potential according to individual interests and abilities, while fostering creativity and self-expression. Art learning not only emphasizes creative skills but also embeds local cultural values as sources of inspiration, contributing to the formation of cultural identity among youth. Guided by Bruce J. Cohen’s enacted role theory, Sekolah Seni Tubaba functions as a vital platform for strengthening and sustaining local cultural identity through inclusive and participatory art education